A membrane-bound ankyrin repeat protein confers race-specific leaf rust disease resistance in wheat - Markus C. Kolodziej (Nature Portfolio, 2021)
Winter wheat cultivar Forno harbors a race-specific leaf rust resistance locus Lr14a, but the causative gene is unknown. Here, the authors show that Lr14a encodes a membrane-localized protein containing ankyrin repeats and Lr14a-containing segments have been introgressed into the bread wheat gene pool multiple times.